Tort Litigation Versus Mediation in Medico-Legal Disputes: Evaluating The Limits Of Mediation and Proposals for Reform - Siti Farahiyah Ab Rahim; Anggraeni Endah Kusumaningrum (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 2 Page (176–197)